A Civil Body Politick: Governance, Community, and Accountability in Early New England - Aleksandrov, Gleb V. (Frontiers in Political Science, 2022)
In the early XVII century, when the New England colonies were established, the English Crown, preoccupied with domestic matters, interfered little with matters of colonial administration. The government system created by the colonists, was inspired to a certain degree by the religious ideas shared by many Puritan colonists but was shaped by political necessity and social conditions specific to the colonies. This created a system characterized by a much higher degree of accountability than in England, ensured by numerous checks on government power, both formal and informal. The same principles, initially applied to governance in individual settlements were later used for the colonies and the Confederation of New England, the first major inter-colonial political union. Early New England serves as an example of practical application of ideas in many ways similar to (and in many ways drastically different from) what we today call democracy as a foundation of ultimately successful government. By modern standards, the representative nature of the New England government was very limited, since it excluded women, Native Americans and other marginalized groups from the political process. It was also deeply rooted in a specific set of religious ideas. Nevertheless, the principles of elected representative government, present in some form in many Western polities, rarely served as a foundation of those political systems, still in most cases monarchies with limited government accountability. In New England these principles formed the core of the government system. This essay explores the formation of the early New England political system, its underlying ideas, both religious and secular, the way it faced some of the challenges encountered in the first decades of English settlement in the New World, and its eventual dissolution under external pressure.